AMERICAN CONSERVATISM IN THE CONTEXT OF GLOBALIZATION IN OUR HOME: OPPORTUNITIES AND DANGERS - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2012)
Conservatism is a very interesting issue to be studied. Moreover, conservatism is often seen with a negative connotation. This is reasonable because conservatism is a term that is quite elusive and often debated. This paper focuses on the cultural-philosophical dimension of globalization and the cultural traits of American conservatism. Moreover the world today is on the threshold of a new global capitalism, one which constitutes not only opportunities, but keep risks for development. The opportunities for development and great risks are found in all dimensions of globalization. In this case, humans are positioned as main actors on how to preserve the cultural traits. They can be agents of determinism in their home. In addition Indonesia has experienced the same process of global evolvement as many other countries have. Democracy, fairness, intellectual improvement and dedication towards an independent country considered as recent values, are from the inter-relation of thoughts and cultures between Indonesia and other countries. Key words: Gilded age, individualism, cultural traits, global era, conservatism